„Raport do El Greca” Nikosa Kazantzakisa zagubiony w tłumaczeniu (Report to Greco by Nikos Kazantzakis Lost in Translation) - Bzinkowski, Michał (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2025)
In this essay, I analyse selected excerpts from the Polish edition of Nikos Kazantzakis’s Report to El Greco (2012), which was translated not directly from Greek but from an English text. My aim is to show what dangers await the translator when he omits the source text and the implications this has on the target text and, consequently, on the reception of the translated work. I focus mainly on the following issues: the incompleteness of the target text and content deficiencies in relation to the source text; the content inadequacy of the target text, the lack of lexical and phraseological equivalence; the lack of equivalence at the level of cultural references. The analysis reveals significant discrepancies, which are not limited to omissions or far-reaching paraphrases, but touch upon the core of Kazantzakis’ work, his key philosophical concepts, which are almost completely misrepresented in the Polish edition.